Patience is the key: Contraceptive induced chorea in a girl with Down Syndrome. (July 2016) - Eggink, Hendriekje; Kuiper, Anouk; Delnooz, Cathérine C.S.; Sival, Deborah A.; de Koning, Tom J.; Tijssen, Marina A.J.
Abstract: Background: Isolated (sub)acute chorea in young patients is a relatively rare movement disorder with a broad differential diagnosis, including drug-induced, post-infectious, auto-immunological and vascular aetiologies. Case presentation: We describe an adolescent girl with Down's syndrome presenting with chorea due to oral contraceptive usage. After discontinuation of the oral contraceptive it took several months before the symptoms disappeared. Although generally well recognised, it is important to realise this delayed effect. Rejecting the diagnosis too soon may lead to unnecessary treatment for other possible underlying aetiologies, especially in patients with Down Syndrome, known to be vulnerable for autoimmune disorders. Conclusion: We plead for discontinuation for at least three months before exclusion of oral contraceptives as cause of chorea. Highlights: Oral contraceptives should be considered is a cause of chorea in adolescents. Cessation of oral contraceptives leads to disappearance of chorea. Oral contraceptives should be discontinued for at least three months.